System of activities that contributes to the environmental education for sustainable development of 6th-grade students through an environmental club in English Language - Berges Coma, Dayan (Universidad de Ciencias Pedagógicas "Félix Varela Morales", 2015)
This paper presents a system of activities to be developed with elementary school students through an environmental club in English language with the purpose of enhancing their environmental education in terms of knowledge, motivation and attitudes. A theoretical and methodological background on the topic is provided including the concepts of environment, sustainable development, and environmental education, as well as the most outstanding global and local environmental issues nowadays. A needs assessment was carried out by means of empirical methods like the pedagogical test, the survey, and the scientific observation. The results revealed that the sample of students had very limited knowledge on environmental issues and that their attitudes towards the environment needed to be corrected. Accordingly, a system of activities was designed to meet such needs, including appealing activities that imply active involvement in environmental protection along with language learning.

Cet article présent un système d'activités à développer avec les élèves des écoles élémentaires à travers un club environnemental en langue anglaise dans le but d'améliorer leur éducation à l'environnement en termes de connaissances, la motivation et les attitudes. Un fond théorique et méthodologique sur le sujet est fourni, y compris les concepts de l'environnement, le développement durable et l'éducation environnementale, ainsi que les questions les plus remarquables écologiques locales et mondiales de nos jours. Une évaluation des besoins a été effectuée au moyen de méthodes empiriques comme le test pédagogique, l'enquête et l'observation scientifique. Les résultats ont révélé que l'échantillon des étudiants avait une connaissance très limitée sur les questions environnementales et que leurs attitudes à l'égard de l'environnement devaient être corrigées. En conséquence, un système d'activités a été conçu pour répondre à ces besoins, y compris des activités attrayantes qui impliquent une participation active dans la protection de l'environnement ainsi que l'apprentissage des langues.
Keywords: Lenguas Extranjeras; Inglés; Sistema de Actividades; Educación Primaria; Enseñanza; English; Medio Ambiente